Augmented Reality meets Non-Fungible Tokens: Insights Towards Preserving Property Rights - Duguleană Mihai; Gîrbacia Florin (IEEE, 2021)
Non-fungible tokens are one of the newest use-cases of blockchain technology. Ethereum Virtual Machine (EVM)-based blockchains such as Ethereum, Binance Smart Chain (BSC), or Polygon/Matic have standardized this type of tokens using interfaces such as ERC721 and ERC1155. This development fostered a connection between blockchain and Mixed Reality technologies, which can now coexist in cohesive applications. In this paper, we present the opportunities and challenges resulting from using Augmented Reality NFTs, with a particular focus on the preservation of property, whether it is physical or purely digital. We present a methodology that can ensure the protection of privacy and the preservation of intellectual property when transitioning assets from the virtual to the physical world.
Keywords: augmented reality; blockchain; property rights